1994
DOI: 10.1073/pnas.91.23.10873
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vpr regulates productive infection and latency of human immunodeficiency virus type 1.

Abstract: In human immunodeficiency virus (HIV)-positive individuals, the vast majority of infected peripheral blood cells and lymph node cells may be latently or nonproductively infected. The vpr open reading frame of HIV-1 encodes a 15-kDa virion-associated protein, Vpr. The vpr gene has been shown to increase virus replication in T cells and monocyte/macrophages in vitro. We have previously reported that vpr expression in various tumor lines leads to growth inhibition and differentiation, indicating that Vpr may func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
210
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(212 citation statements)
references
References 46 publications
2
210
0
Order By: Relevance
“…2C). Together, these findings demonstrate the usefulness of R96 for detection of viral Vpr in serum samples of HIV-infected individuals (23).…”
Section: Analysis Of Svpr By Protein Sequencing Ms and Westernmentioning
confidence: 75%
See 1 more Smart Citation
“…2C). Together, these findings demonstrate the usefulness of R96 for detection of viral Vpr in serum samples of HIV-infected individuals (23).…”
Section: Analysis Of Svpr By Protein Sequencing Ms and Westernmentioning
confidence: 75%
“…Recombinant Vpr has been produced in insect cells and as a glutathione S-transferase fusion protein in Escherichia coli (15). At concentrations as low as 100 pg/ml, the extracellular addition of recombinant Vpr activates HIV-1 replication in both leukemic cell lines and primary peripheral blood mononuclear cells (23,24). However, when maintained at high concentrations as required for structural investigation, preparations of recombinant Vpr often undergo spontaneous aggregation.…”
mentioning
confidence: 99%
“…Recently, we also found that Vpr is present in serum of HIV-1-positive patients (Levy et al, 1994) at the concentration of about 0.7 nM (Hoshino et al, submitted). In the current study, we used 3.7 nM of rVpr to obtain the definite activity inducing DSBs, but it would be possible that the high concentration of Vpr is present in the foci of HIV-1 infection, suggesting that DSBs can be generated in the cells within HIV-1-positive patients.…”
Section: Biological Relevance Of Vpr-induced Dsbs and Hr For Hiv-1 Inmentioning
confidence: 79%
“…For instance, a functional Vpr protein has been purified from serum and cerebrospinal fluid of infected patients. 8 The purified Vpr has been shown to have transactivational and cytotoxic properties in CD4 þ T cells and neurons, respectively. [8][9][10] Such results suggest that Vpr's cellular effects can manifest through various mechanisms including entry of free Vpr into uninfected, activated CD4 þ T cells for destruction.…”
Section: Introductionmentioning
confidence: 99%